Research on Carbon Unlocking Pathway in Sichuan Province under the Background of “Dual Carbon” - Huang, Zhijin; Ding, Yi; Pang, Min; Liu, Ke; Liu, Fei (International Journal of Natural Resources and Environmental Studies, 2024)
In the progress of realizing green development and transformation, many difficulties exist in Sichuan Province, such as low level of ‘carbon unlocking’, unbalanced development of ‘carbon unlocking’ among regions, and insufficient systematic coordination and governance capacity. So, this paper from technology, system and industry and other aspects, based on the ‘double carbon’ goal of Sichuan Province, to construct the ‘carbon unlocking’ mechanism with the characteristics of Sichuan Province, to create a ‘multi-body-multi-path’ synergistic mechanism. This will help to promote green technology innovation and help to achieve the ‘dual-carbon’ goal on schedule.